Luisia trichorrhiza (Hook.) Blume - An Addition to the Orchid Flora of Maharashtra, India - Muratkar, G. D.; Govekar, R. S.; Sardesai, M. M. (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract.